Characterization, enhancement and modelling of mannosylerythritol lipid production by fungal endophyte Ceriporia lacerate CHZJU. (1st August 2017) - Niu, Yongwu; Fan, Linlin; Gu, Di; Wu, Jianan; Chen, Qihe
Highlights: Ceriporia lacerate CHZJU can produce mannosylerythritol lipid. Mannosylerythritol lipid A produced by Ceriporia lacerate CHZJU is the major type. Optimization using response surface methodology enhances mannosylerythritol lipid. Fermentation kinetic modelling for mannosylerythritol lipid production was developed. Abstract: The glycolipid biosurfactants mannosylerythritol lipids (MELs) attract great attention for their biodegradability, super emulsifying properties and versatile bioactivities. In this study, the MEL deriving from Ceriporia lacerate CHZJU was identified as MEL-A, and its critical micelle concentration and emulsifying activities were assessed. To examine the production of MELs from Ceriporia lacerate, a Plackett-Burman design and response surface methodology were used to optimize the culture nutrients. The optimal medium contains 1 g/L yeast extract, 1.5 g/L (NH4 )2 SO4, 0.5 g/L KH2 PO4, 0.04 g/L CaCl2, 119.6 mL/L soybean oil and 0.297 g/L MnSO4 . Subsequent verification revealed that the yield of MELs was 129.64 ± 5.67 g/L. Furthermore, an unstructured kinetic model was developed for mycelial growth, MEL production and substrate utilization. This work provides insight into Ceriporia lacerate CHZJU, a predominant fungus producing MEL-A. Optimization using response surface methodology enhanced the mannosylerythritol lipid recovery. Importantly, we developed fermentation kinetic modelling for mannosylerythritol lipid production.